Compliance with universal precautions by emergency room nurses at Maharaj Nakorn Chiang Mai Hospital - Picheansathian W. (2014)
Compliance with universal precautions (UP) by emergency room nurses in Maharaj Nakorn Chiang Mai Hospital was studied between August 1, 1992 and November 30, 1992. Data were gathered from observation, questionnaires, and focus group discussion. During a period of 3 months, 23 registered nurses and 17 practical nurses were observed during performing 509 UP-specific nursing procedures. Results showed a low rate of compliance with universal precautions among emergency room nurses. Aside from handwashing, the compliance of registered nurses was significantly higher than that of the practical nurses: 58% and 18%, respectively (P < 0.05). The most common protocol violations involved the use of barrier precautions. Gloves were the only protective attire that were worn while carrying out nursing interventions; other protective attire was completely ignored. The results also indicated that some nurses, both registered and practical, still recapped needles and demonstrated low rates of compliance with recommended handwashing procedures. In addition, they were more likely to apply the recommended universal precautions for patients with known HIV infection. The reasons for not using protective attire were similar for both registered and practical nurses i.e.: supplies not available, insufficient time, discomfort, inconvenience, habit, believing UP were not necessary, and concerns about patients' feeling and about nurses' own appearance. The findings also indicated that many emergency room nurses did not understand the implication of the UP for practice and had never participated in an inservice education programme related to UP.